2013
DOI: 10.1088/0953-4075/46/16/164030
|View full text |Cite
|
Sign up to set email alerts
|

Double core-hole formation in small molecules at the LCLS free electron laser

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
3
15
0
Order By: Relevance
“…and |χ S DCH ij ( k, k , t) are the nuclear wave packets associated with the ground, the SCH and the DCH states, respectively. Satellite states are not considered in the present work even if they can be found in the same energy region as DCH resonances [10,13,36], because they can be circumvented by measuring in coincidence the two photoelectrons.…”
Section: A Equations Of Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…and |χ S DCH ij ( k, k , t) are the nuclear wave packets associated with the ground, the SCH and the DCH states, respectively. Satellite states are not considered in the present work even if they can be found in the same energy region as DCH resonances [10,13,36], because they can be circumvented by measuring in coincidence the two photoelectrons.…”
Section: A Equations Of Motionmentioning
confidence: 99%
“…Due to the very recent development of XFELs, only few observations of DCH states have been carried out. Most investigations concern atoms [2,[5][6][7][8][9], or multiply core ionized small molecules [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Double-core hole states have recently been experimentally realized in the gas phase [57,75]. Creation of double-core hole states in water should hence be possible with the intensities available at XFELs and pulses of a few femtoseconds.…”
Section: High Fluence Effects and Nonlinear X-ray Spectroscopy In Watermentioning
confidence: 99%
“…It has shown that it has greater potential to probe the local chemical environment than by detecting single corehole (SCH) spectroscopy. Secondly, combining with accurate theoretical simulations [14], DCH spectroscopy provides a useful tool for estimating or even diagnosing the intensity and duration of x-ray pulses [15]. In dense plasmas, it reflects the screening effects on atoms embedded in the plasmas produced by x-ray laser pulses [16,17,18,19] and thus it can be utilized to deduce the environmental effects.…”
Section: Introductionmentioning
confidence: 99%